Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Siswa Kelas V Tema 8 (Lingkungan Sahabat Kita) - Mahrus Al Hadi; Conny Dian Sumadi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The purpose of this study was to find out: 1) The Implementation Model of Problem Based Learning on Student Learning Outcomes in Class V Theme 8 (Our Friendly Environment). 2) The Effect of Problem-Based Learning Models on Student Learning Outcomes in Class V Theme 8 (Our Friend's Environment). This study used a Quantitative method with a Pre Experimental Design type with a One Group Pre test-Pos test Design design type. The population of this study was fifth grade students for the 2022/2023 Academic Year. The sample in this study used Nonprobability Sampling, a saturated sample type. The sample of this research is 19 students. Data was collected using a written test. it can be concluded that testing the hypothesis using the t-test obtained tcount = 2.173 and table value = 2.093. This means that tcount > ttable or 2.173 > 2.093, and the results are Sig (0.043 <0.05). means H0 is rejected and Ha is accepted. So it can be stated that there is a significant influence between the Problem Based Learning model on the learning outcomes of class V students.